The Handling of Credit Problems in Bank Financial Restruction - Kaukazu Shimura (Jurnal Akta, 2023)
The effort to minimize potential losses from problem loans is that banks can carry out credit restructuring. Implementing credit restructuring for problem loans means that debtors can again fulfill their obligations to the bank, namely in the form of paying principal installments and/or credit interest which has been given relief tailored to the debtor's capabilities. The result of credit restructuring is that the debtor's business continuity becomes viable again so that the debtor can fulfill his obligations to the bank. The obstacles that arose in the restructuring process were able to be overcome by the bank optimally and proportionately. The solution adopted is also a method that is profitable for both parties, so that both parties (debtor and creditor) avoid the element of loss.